2021
DOI: 10.5005/jp-journals-10078-1295
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Central Corneal Thickness Measurements by Contact and Non-contact Pachymetry Devices

Abstract: A bstract Aim and objective To compare central corneal thickness (CCT) measurements obtained by handheld contact ultrasound pachymetry (HCUP) and non-contact pachymetry devices. Materials and methods Ninety eyes of 90 patients (52 male and 38 female) were included in the study. Measurements from two non-contact devices, —specular microscopy (SM, Konan Medical, CA, USA) and Oculus Pentacam (Oculus Inc., Germany)—were compared against HCUP (Pach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Previous studies have similarly found that CCT measurements with ultrasound are slightly thicker than with optical biometers. 13,[24][25][26] Although statistically significant, the small overall difference in CCT between the PM1 and UP is not clinically significant; however, the 95% LoA ranging from 9.47 μm above to 24.63 μm below would suggest that the two devices are not directly interchangeable and therefore the same device should be used when monitoring CCT over time. Similar results have also been found in agreement studies using optical coherence tomography (OCT), which is currently widely used for quantitative and qualitative evaluation of anterior segment structures in a variety of clinical settings.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have similarly found that CCT measurements with ultrasound are slightly thicker than with optical biometers. 13,[24][25][26] Although statistically significant, the small overall difference in CCT between the PM1 and UP is not clinically significant; however, the 95% LoA ranging from 9.47 μm above to 24.63 μm below would suggest that the two devices are not directly interchangeable and therefore the same device should be used when monitoring CCT over time. Similar results have also been found in agreement studies using optical coherence tomography (OCT), which is currently widely used for quantitative and qualitative evaluation of anterior segment structures in a variety of clinical settings.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have similarly found that CCT measurements with ultrasound are slightly thicker than with optical biometers. [20][21][22][23] Although statistically significant, the small overall difference in CCT between the PM1 and ultrasound biometry is not clinically significant, however the 95% limits of agreement ranging from 9.47 µm above to 24.63 µm below would suggest that the two devices are not directly interchangeable and therefore the same device should be used when monitoring CCT over time. Similar results have also been found in agreement studies using optical coherence tomography (OCT), which is currently widely used for quantitative and qualitative evaluation of anterior segment structures in a variety of clinical settings.…”
Section: Discussionmentioning
confidence: 95%
“…Finally there is the toxicity of topical anaesthetic agents which are necessary for ultrasound pachymetry [18] . Apart from ultrasound pachymetry a number of non-contacttechniques have been developed and established which are able to measure CCT [9,[11][12][19][20][21][22][23][24][25] . The goal of this study was to evaluate the feasibility of different techniques to measure CCT in the perioperative course of uneventful cataract surgery using phacoemulsification.…”
Section: Measuring Corneal Thickness Perioperatively Using Three Diff...mentioning
confidence: 99%
“…This results in corneal swelling and thereby an increase in central corneal thickness (CCT) as an expression of endothelial decompensation. Extent and decrease of corneal swelling prove the endothelial recovery and compensation of its function [3,[6][7][8][9][10][11][12][13][14] . A high preoperative endothelial cell count (ECC) does not guarantee an uncomplicated intra-and postoperative course and a low ECC does not make corneal complications not inevitable.…”
Section: Introductionmentioning
confidence: 99%